The role of job satisfaction in mediation the effect of self-efficacy and job insecurity on turnover intention - Narotama, Ida Bagus Indra; Sintaasih, Desak Ketut (International research journal of management, IT and social sciences, 2022)
This study aims to determine the role of job satisfaction in mediating the effect of self-efficacy and job insecurity on the turnover intention of facility care employees at PT. Angkasa Pura Supports Denpasar Branch. This research was conducted at PT. Angkasa Pura Supports Denpasar Branch with a sample of 218 employees. Methods of data collection using interviews and questionnaires. Determination of the sample using proportionate random sampling. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results showed that self-efficacy had a negative and significant effect on turnover intention. Job insecurity has a positive and significant effect on turnover intention. Self-efficacy has a positive and significant effect on job satisfaction. Job insecurity has a negative and significant effect on job satisfaction. Job satisfaction has a negative and significant effect on turnover intention. Job satisfaction partially mediates the effect of self-efficacy on turnover intention. Job satisfaction also partially mediates the effect of job insecurity on turnover intention.